2015
DOI: 10.1007/s10549-015-3521-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 induces cancer stem cell phenotype in breast cancer cell lines

Abstract: Heat shock factor 1 (HSF1) has long been recognized as the master transcription factor that regulates heat shock proteins (HSPs).  More recently HSF1 has been associated with a broader role in regulating response to a variety of cellular stresses beyond heat-shock.  We previously found that high HSF1 expression is associated with poor outcome in lung, breast and colon cancers. Importantly, however, the HSF1 signature correlated with poor outcome in these studies was not related to the heat shock response, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…In breast cancer, nearly 80% of in situ and invasive breast carcinomas expressed high levels of HSF1, which was associated with a high histological grade, a larger tumor size, and nodal involvement; those with HSF1‐positive tumors had significantly reduced survival rates compared with women with HSF1‐negative tumors (Santagata et al ., ). A subsequent study revealed that in breast cancer cell lines, the overexpression of HSF1 induced an augmentation of the cancer stem cell markers and conferred resistance to chemotherapeutic drugs (Wang et al ., ). Here, we showed that pancreatic cancer expressed a high level of HSF1, which is similar to other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, nearly 80% of in situ and invasive breast carcinomas expressed high levels of HSF1, which was associated with a high histological grade, a larger tumor size, and nodal involvement; those with HSF1‐positive tumors had significantly reduced survival rates compared with women with HSF1‐negative tumors (Santagata et al ., ). A subsequent study revealed that in breast cancer cell lines, the overexpression of HSF1 induced an augmentation of the cancer stem cell markers and conferred resistance to chemotherapeutic drugs (Wang et al ., ). Here, we showed that pancreatic cancer expressed a high level of HSF1, which is similar to other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HSF1 has also been shown to be involved in hepatocellular carcinoma development [3], as well as induction of a CSC-like phenotype in breast cancer cells [5]. A greater understanding of CSCs will be important for the diagnosis and treatment of cancer as well as for future drug development [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, if there exists a subpopulation of slow-cycling cells in a tumour, this subpopulation is more likely to survive chemotherapy and proliferate post treatment, despite having a slower production rate. Such a slow-cycling subpopulation may comprise CSC-like cells, as slow-cycling cells have been linked to cancer stem cells [40],which in turn have been conferred with reduced sensitivity to chemotherapeutic drugs [78]. Previous research indicates that cancer cells may obtain stem-cell like traits [16], in fact non-stem cancer cells may convert into CSC-like cells seemingly spontaneously, as demonstrated in vivo by Chaffer et al [12].…”
Section: Cell Cycle Mediated Drug Resistance By Slow-cycling Cellsmentioning
confidence: 99%
“…Inhibiting Hsp27, Hsp70, Hsp90 has been hypothesised as part of future treatment plans [29,65] and moreover Hsp70 has been suggested as a factor to prognostically evaluate the risk of disease recurrence [45]. The heat shock factor 1 protein (HSF1) regulates Hsps [65,78], and HSF1 overexpression is linked to poor prognosis in breast, lung and colon cancers, an increase in intratumoural cancer stem cells proportions and chemotherapeutic drug resistance [78]. Specifically, cells with high HSF1 levels have displayed increased paclitaxel resistance [78].…”
Section: Induced Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation